Electrochemotherapy: an effective local treatment of cutaneous and subcutaneous melanoma metastases. Issue 3 (24th September 2013) - Ricotti, F.; Giuliodori, K.; Cataldi, I.; Campanati, A.; Ganzetti, G.; Ricotti, G.; Offidani, A.
Abstract Treatment of multiple cutaneous and subcutaneous melanoma metastases is still represents a therapeutic challenge for both dermatologists and oncologists. Electrochemotherapy (ECT) is a promising therapeutic procedure, owing to its ability to improve the penetration of cytotoxic drugs into cancer cells by application of current electric pulses. The aim of our study is to evaluate efficacy, tolerability and long‐term efficacy of ECT in the treatment of advanced metastatic melanoma. Thirty patients affected by a total of 654 cutaneous and subcutaneous melanoma metastatic nodules were recruited. All patients were treated after they had undergone to a mild general anesthesia. Intravenous Bleomicina solution was administered 8 minutes before the application of electric pulses, generated by a Cliniporator TM (the device validated for ECT). The objective response rate of 100% (67.28% complete response and 32.72% partial response) was observed. A total of 214 metastatic lesions from 24 patients received a second ECT session, among them 141 showed a further complete response. Twenty‐four months later, the local tumor control rate was 72%. The results of this study seem to demonstrate that ECT is an effective and valid therapeutic tool for the treatment of cutaneous metastases from melanoma. ECT can be considered a first‐line palliative treatment since it is able to alleviate pain and reduce the tumor's spontaneous bleeding with a significant improve of patients' quality of life.